335 Planned Surgery in the COVID-19 Pandemic: A Prospective Cohort Study from Nottingham. (4th May 2021) - Catton, J; Banerjea, A; Gregory, S; Hall, C; Crooks, C; Lewis-Lloyd, C; Marshall, A; Humes, D
Abstract: Introduction: Globally planned surgical procedures were deferred during the current COVID-19 pandemic. We aim to report planned urgent and cancer case outcomes during the pandemic using a multi-disciplinary prioritisation group. Method: Prospective cohort of patients prioritised by a multi-disciplinary COVID Surgery group undergoing urgent or cancer surgery at a NHS Trust from 1 st March-30 th April 2020. 30-day post-operative rates of PCR positive and suspected COVID-19 infections, 30-day mortality and COVID-19 related deaths are reported. Results: During the period, 597 patients underwent surgery, median age 65-years (interquartile range 54-74) of which 86% (514/597) had a cancer diagnosis. 61% (362/597) had surgery at the NHS Trust whilst 39% (234/597) had surgery at Independent Sector hospitals. The COVID-19 incidence in the East Midlands was 193.7 per 100, 000 population. 30-days following surgery, 1.3% (8/597) tested COVID-19 positive with all cases at the NHS site. 30-day mortality was 0.7% (4/597). Mortality following PCR positive COVID-19 diagnosis was 25% (2/8). Including PCR positive and suspected cases 3.0% (18/597) developed COVID-19 infection, 1.3% at the independent site compared to 4.1% at the NHS Trust (p = 0.047). Conclusions: Rates of COIVD-19 infection in the post-operative period were low especially in the Independent Sector site. Mortality following a post-operative diagnosis of COVID-19 was high.